PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DESAIN PEKERJAAN DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DIMODERASI OLEH TEKNOLOGI PADA GENERASI MILENIAL DI INDUSTRI PENDIDIKAN - Hayati, Puput Nurul; Putriana, Lies; Salim, Fahruddin (Universitas Indo Global Mandiri Palembang, 2021)
The quantity of millennial generation is increasing every year, including the working millennial generation. At work, millennial generation satisfaction is still lower than the generation above. Job satisfaction is an important aspect that companies need to evaluate because it will affect employee performance, which ultimately leads to employee loyal ty or turn over. According to Robbins & Judge (2017) and Armstrong (2014), factors that affect job satisfaction are leadership, job design, career development, coworkers, and work environment (one of which is technology).The purpose of this study was to analyze the influence of transformational leadership, job design, and career development on job satisfaction of millennial generation employees with technology moderation. This research was conducted by distributing gform questionnaires to 205 respondents from the millennial generation in the education industry, in Jakarta. The results of this study explain that the variables of transformational leadership, job design, career development and technology can affect job satisfaction by 80%, the rest is influenced by other factors.The variables of transformational leadership, job design, career development and technology have a significant positive effect on job satisfaction variables. Meanwhile, the technology variable as a moderating variable does not have a significant effect in moderating exogenous variables against endogenous variables.